Impact of corporate governance principles on financial Performance: evidence from listed financial companies in Sri Lanka - Nalinda, J.M.D.P.; Dissanayake, D.H.S.W.; Balagobei, S. (Sabaragamuwa University of Sri Lanka, 2019)
This study aims to examine the impact of corporate governance (CG) principles on financial performance of listed financial companies in Sri Lanka. This study is based on quantitative approach and using a panel data of 32 listed financial companies for the period of 2012-2016 and Return On Asset (ROA) and Return On Equity (ROE) as proxies to financial performance, the hypotheses were tested to investigate the influence of compliance of the corporate governance on the financial performance of Sri Lankan listed financial companies. Secondary data for the compliance of corporate governance principles were extracted. CG Score was constructed to measure the degree of compliance of corporate governance and panel data regression analysis and Pearson’s correlation analysis were employed to test the hypothesis. The results reveal that CGS which is an aggregate of the compliance requirements of the corporate governance principles positively impact on financial performance which is measured by ROA and ROE whereas only directors’ remuneration and relations with shareholders have a significant positive impact on financial performance of listed financial institutions while the size of the company, sales volume, number of years the company has operated in the market are keeping as the controlling factors. These results are useful to corporate governance regulators, boards and policymakers to improve corporate governance practices in Sri Lanka.
Keywords: Corporate Governance Principles; Corporate Governance Score; Directors’ Remuneration; Sri Lanka